The process of counseling and psychotherapy matter of skill - Welch, Ira David (Brooke/Cole, 1999)
Combining a research-based overview of the process of counselling with the varied skills the counsellor needs along the way, this book aims to cover what beginning counsellors need to know before meeting their first clients.